UPACARA ADAT SEDEKAH LAUT di Pantai Cilacap - Suryanti, Ani (Sabda: Jurnal Kajian Kebudayaan, 2008)
The Ceremony of Sedekah Laut is a traditional event held annually in Syura or Muharram month on Javanese calendar Tuesday or Friday Kliwon by fisherman community in Cilacap of Central Java to thank God for His blessings. This paper describes the practice of Sedekah Laut and its function for the Cilacap people. The data are taken through participatory observation in the Sedekah Laut event. The result shows that the ritual has several functions for the society covering social, cultural, economic, as well as religious dimensions. Special functions of the ceremony are as to express gratitude to God the Almighty for His generosity of blesssing the community with abunndant of fish subsistence and as to pray for life safety.